Controlling the Resolution of Static Mass Spectrometers Using Intermediate Slit Diaphragms - Antonov, A. S.; Berdnikov, A. S.; Gall, L. N.; Sachenko, V. D. (Journal of analytical chemistry (New York, N.Y.), 2019)
The paper shows how to increase effectively the resolving power and transmission of a static mass spectrometer (i.e., to get an optimal compromise between these two parameters) using the properly positioned intermediate slit diaphragms in order to ensure a minimum loss of sensitivity of the device.